Practical Methods of GIS for Archaeologists: Viewshed Analysis – The Kingdom of Pylos example - George D. Malaperdas (Geoplanning: Journal of Geomatics and Planning, 2021)
Visibility (or Viewshed) Analysis in archeology is a function given through GIS, in purpose to contribute in the field of archaeology and especially in landscape archeology, by reconstituting the visual panorama of a study area of the past.  The concept of landscape archeology is a multidimensional research process that is not limited to archaeologists but places a special emphasis on a multidisciplinary approach. Mycenaean Messenia was the area of study and analysis of the visual panorama for two important reasons. First of all, it is a large area, which presents territories of varying heterogeneity in terms of morphology, while having a large sea front and an open observation horizon. Secondly, it is one of the continental regions of the Mycenaean period, which has evoked the largest number of residential facilities, structures and tombs, and also has been extensively studied by archaeologists since the 1920s. The main aim of this paper is to make an effort to identify archaeological information, through the bibliographic references of the archaeologists who studied the area, with the GIS visibility analysis. For that reason, the author tries for those residential locations that have been assigned a role or function of the site by archaeologists, such as an observation station, to be controlled in parallel and on the basis of new technologies (GIS and Viewshed Analysis) if this view is verified.